A SCIENTIFIC ANALYSIS OF CURRENT GLOBAL ECONOMIC TRENDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The global economy is undergoing a complex transformation driven by multiple interrelated factors, including the post-pandemic recovery, rising inflationary pressures, and technological advancements. This study presents a scientific analysis of recent economic trends, focusing on empirical data and theoretical frameworks. Using contemporary economic articles and reports as primary sources, the research explores the dynamics of inflation, global recovery, and the role of technological innovation in shaping future economic outcomes. The analysis highlights the uncertainty introduced by geopolitical tensions and suggests strategies for policymakers to mitigate risks and foster sustainable growth.